New approaches to diagnosis and arthroscopic management of partial-thickness cuff tears - Rudzki, J. R.; Shaffer, B. (Clinics in Sports Medicine, 2008)
Partial-thickness cuff tears (PTCTs) are increasingly recognized as a source of pain and athletic impairment, especially in overhead athletes. 1,2 Improvements in diagnostic imaging have enhanced the ability to detect and quantify partial cuff disease, and arthroscopic advances have led to novel techniques by which partial cuff tears can be repaired. 2-6 Despite increasing recognition and improved understanding of this condition, the natural history, clinical evaluation, and management of partial tears remain elusive. This is because of the disparity between the extent of partial cuff tearing and the wide variability in clinical impairment and the frequent overlay of concomitant labral and subacromial pathology. When should operating on an athlete with a partial cuff tear be considered? What percentage of cuff tear justifies repair rather than debridement? Does this threshold vary according to the athlete or sport? And if the partial tear is repaired, what can be expected in terms of return to activity, particularly in a high-level thrower? The purpose of this manuscript is to provide an overview of partial cuff tears and their evaluation and management.